Mitochondrial Dynamics and Oxidative Stress-Driven Apoptosis: Cardiovascular and renal Implications from an In Vitro Study - Ali Saqlain Haider, Reja Akram, Irfana Hassan, Muhammad Ahmad Raza Butt, Yamna Fatima, Khadija Kiran, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Mitochondrial dysfunction is increasingly recognized as a driver of cell death incardiovascular and renal pathologies. This in vitro experimental study aimed to examine howperturbations in mitochondrial dynamics contribute to oxidative stress–induced apoptosis in cardiomyocytes and renal tubular epithelial cells